Evaluation of Distortion of ECG Signals after Compression - Němcová, Andrea (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2016)
Evaluation of compression quality is essential part of data compression. No unified approach exists in this area and comparison of different algorithms is very difficult. The paper deals with 13 common efficiency and quality evaluation methods. Two compression algorithms are tested – improved single cycle fractal based algorithm and wavelet based SPIHT algorithm. All the qualityevaluation methods have the same trend for both compression algorithms. For proper evaluation of compressed ECG signal quality, it is recommended to combine various evaluation algorithms.
Keywords: ECG; electrocardiogram; compression; distortion; quality evaluation; signal